1999
DOI: 10.1046/j.1365-2133.1999.03210.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematized porokeratotic eccrine and hair follicle naevus: report of a case and review of the literature

Abstract: We report a unique case of a congenital keratinocytic naevus associated with severe alopecia, onychodysplasia and palmoplantar involvement in a 13-year-old girl. The lesions, consisting of scaly, spinous and verrucous papules and plaques, mainly followed Blaschko's lines and have remained unchanged since birth. The predominant histopathological picture was that of a column of parakeratosis overlying the eccrine ostia and hair follicles. This is the first case of a systematized keratinocytic naevus characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
(33 reference statements)
2
25
0
Order By: Relevance
“…The distribution of PAON plaques along the lines of Blaschko lends support for the role of somatic mosaicism, reflecting clonal expression of abnormal cells derived from the neuroectoderm. 4 Rare studies have looked at potential specific defects in PEODDN, and the relationship of cornoid lamellae to adnexa. Stoof et al 10 found that only ducts within the parakeratotic column stained with carcinoembryonic antigen, whereas the outer wall of the invagination did not.…”
Section: Histogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…The distribution of PAON plaques along the lines of Blaschko lends support for the role of somatic mosaicism, reflecting clonal expression of abnormal cells derived from the neuroectoderm. 4 Rare studies have looked at potential specific defects in PEODDN, and the relationship of cornoid lamellae to adnexa. Stoof et al 10 found that only ducts within the parakeratotic column stained with carcinoembryonic antigen, whereas the outer wall of the invagination did not.…”
Section: Histogenesismentioning
confidence: 99%
“…3,4 Some authors propose that PEHFN and PEODDN are variants of the same process, differentiated by the adnexal structure or structures affected and the level of involvement. 4,9 Examination of multiple level sections in our 5 cases demonstrated that 3 had involvement of both acrosyringia and acrotrichia (cases 1, 2, and 4), suggesting a more accurate diagnosis of PEHFN/PEODDN overlap. It may be that other cases of PEODDN, if examined in this way, might also demonstrate follicular involvement in nonacral lesions.…”
Section: Clinical Differential Diagnosismentioning
confidence: 99%
See 3 more Smart Citations